2016
DOI: 10.5306/wjco.v7.i2.253
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of targeted therapies in oncology

Abstract: Off-label use is defined by the prescription of a marketed drug outside the conditions described in the summary of product characteristics. In oncology, off-label prescribing of targeted therapies may occur in patients with other tumor types expressing the same target. Agents associated to phenotypic approaches such as therapies against the tumoral vasculature (anti-angiogenic drugs) and new immunotherapies (checkpoint inhibitors) also carry the potential of alternative indications or combinations. Off-label u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…This choice is particularly relevant because further analysis of the current study was global and not just US‐centered. Third, off‐label use in oncology has extensively been studied and described, but we chose a slightly different approach, to be more aligned with routine care. Labels are stringently phrased by regulators and off‐label use then occurs as soon as a patient's condition is not strictly similar to the one depicted in the Summary of Product Characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This choice is particularly relevant because further analysis of the current study was global and not just US‐centered. Third, off‐label use in oncology has extensively been studied and described, but we chose a slightly different approach, to be more aligned with routine care. Labels are stringently phrased by regulators and off‐label use then occurs as soon as a patient's condition is not strictly similar to the one depicted in the Summary of Product Characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…but perceived efficacy, toxicity, and quality of life considerations may favor the use of an off-label medication rather than an approved treatment. 2 Off-label prescribing is common across all pediatric disciplines, though may be enriched in specific populations. 3 For example, European studies have shown that at least one-third of children in hospitals and up to 90% of neonates in a neonatal intensive care unit receive off-label therapies.…”
mentioning
confidence: 99%
“…Another aspect, which utilizes genome sequencing, has also been the off‐label use of targeted therapies for patients with a similar single‐ or multi‐marker mutation profile regardless of the tumor origin . This practice is very common in oncologic clinical practice and is frequently referred to as precision medicine .…”
Section: Trends In Drug Selection Strategies For Solid Tumorsmentioning
confidence: 99%